Sustainable maintenance of navigation channel - Olanrewaju, Oladokun Sulaiman (2006)
Maritime industry is the cradle of all modes of transportation, where port and ship are necessary to facilitate trading through marine transportation, recent time has proved that there is continuous growth or need for larger and sophisticated ship through increasing shipping activities and this has lead to design and production of sophisticated state of art, safety oriented marine vehicles, in term of size, speed and structure. Albeit, the rate of growth of ship is out of phase with the condition of navigation channel, the channel due to environmental pressure is subject misplacement of allowance required to keep the channel safe to receive larger target vessel. Channel operators rarely have a simplified system to monitor and exercise to balance safe reception and navigation of large ship in inland water, which are always considered as restricted water, due to exposure to accident that could to environmental disaster. This project seeks to apply various models to Port Tanjung Pelepas (PTP), with thrust to deduce simplified model that will provide insight for port operator on sustainable way to maintain the channel.